Efficacy and tolerability of full spectrum hemp oil in dogs living with pain in common household settings - Panda, Chinmayee; Rathinasabapathy, Thirumurugan; Metzger, Brandon; Dodson, Sheila; Hanson, Dirk; Griffiths, Jody; Komarnytsky, Slavko (Frontiers in Veterinary Science, 2024)
Lameness and restricted mobility are a significant concern in companion animals experiencing chronic pain, inflammation, or age-related pathologies. The growing awareness of health risks and side effects associated with the long-term use of prescription analgesics requires different management strategies to address these issues. In this study, we conducted a crossover evaluation of the effect of full spectrum hemp oil dosed orally at 2 mg/kg BID phytocannabinoids for 8 weeks in dogs (n=37) living with pain in common household settings. Owner-reported canine pain, home activity, accelerometer-based activity, walkway-based gait, and tolerability were assessed at each phase of the study. Secondary endpoints included changes in blood biochemistry, liver enzymes, inflammatory biomarkers, and plasma metabolites. The intervention was positively associated with a decrease in pain scores (-46.2%, p=0.0016), increased ability to walk up and down the stairs (10.6-14.7%, p<0.05), and improved daily activity (25.9%, p=0.0038). Decreases in plasma levels of proinflammatory cytokines TNF-α, IL-6, and IL-8 were also observed. Taken together, these findings suggest that the benefits of nutritional supplementation with hemp oil could include control of pain, greater mobility, and an overall improvement in the animal wellbeing.